IDENTIFY THE USE OF FUTURE TENSE IN RICK AND MORTY SHOW BY JUSTIN ROILAND & DAN HARMON - Sulthan Gibran Junaedy (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2021)
Learning about grammar is essential for EFL students. To different people, the Word Grammar means different things. To the average person, it refers to the correctness or incorrectness of the words they use. It entails a logical and terminological analysis of sentences for a school student. Grammar knowledge helps the student in the correction of errors and the progress of written work. Only through unconscious assimilation can a person learn a foreign language accurately. Learning grammar is essential because it is indispensable for the student. Grammar is the system of a language. Grammar is often referred to as a language's "rules," but no language has rules. When we say "rules," we mean that someone made the rules first and then spoke the language, as if it were a new game. Languages, on the other hand, did not begin in this manner. Moreover, in the English language, there are verbs. There are three tenses for verbs: past, present, and future. Things that have already occurred are described in the past (e.g., earlier in the day, yesterday, last week, three years ago). The present tense is used to describe events that are taking place or that are ongoing. Things that have not happened yet are defined in the future tense (e.g., later, tomorrow, next week, next year, three years from now). EFL students need to watch the materials in order to enhance their capacity as speakers. Rick and Morty are well-known TV shows. A future tense (abbreviated fut) is a verb form in grammar that usually indicates that the event represented by the verb has not yet occurred but is expected to occur in the future. This TV show contains many data about the future tense that will be analyzed. This paper aims to find the future tense in a TV show called Rick and Morty. It uses the descriptive qualitative method. Future tense with the word "will" is discovered to be the most commonly occurring data.